A theoretical study on hybrid ultra-high molecular weight polyethylene for use in pin-shaped steel backing gear teeth of a cycloid drive. (November 2015) - Peng, X.; Wu, C. L.; Chen, Z. H.
Abstract : To improve performances of cycloid drive in a sluice hoisting equipment, pin-shaped steel backing gear teeth composite structure using ultra-high molecular weight polyethylene was designed. Based on the viscoelasticity of ultra-high molecular weight polyethylene material, geometric models and mechanical models of the hybrid polymer pin tooth were built up in this paper. Meanwhile, the model of traditional steel pin tooth was built up for comparison. Through the comparative analysis of the stress distribution and carrying capacity by using the simulation module of Inventor, it was proved that the composite structure polymer pin teeth can significantly reduce the contact stress and provide superior mechanical properties to the traditional cycloid drive, being an effective method to optimise the low-speed overloaded cycloid drive.